Reflections on crime and class - Mead, Ed (Social justice, 2000)
Part of a special issue on critical resistance to the prison-industrial complex. The writer discusses the relationship between crime and class. He contends that punishments of crime can differ just as definitions of crime can vary according to the class basis of the existing social order. Furthermore, he argues that the introduction of increasingly cheaper and more available surveillance technology and alarm systems will force crime to be steadily pushed deeper into the poorest minority communities.